ANALISIS”NILAI”PENDIDIKAN KARAKTER”PADA NOVEL PENDEK“PUDARNYA”PESONA”CLEOPATRA KARYA HABIBURRAHMAN EL SHIRAZY - Devi Sri (IKIP Siliwangi, 2020)
This study intends to describe the character values in the short novel entitled”Faded Pesona Cleopatra”by Habiburrahmman El Shirazy. The method used is descriptive qualitative. The data souce that the researchers took was a short novel entitled Pudarnya PTRA Cleopatra by Habibburahman El Shirazy. Data retrieval is done by understanding and reading the short novel carefully and the researcher makes an important note of the values contained in the character education in the short novel. This data analysis was carried out by researchers following the Miiles & Hubermen model, where the firsh researcher identified a short fading novel of Cleopatra’s charm as an object to be atudied, the second the researcher would carry out a reduction in the data, and the third when the researcher presented the data, and the fourth interpreted the data according to theory, and finally the researchers draw conlusions. Furthermore, the results of this study indicate the in this shoet novel entitled Cleopatra’S has seven values of character education including (1) religius values, (2) moral values, (3) values in honesty, (4)0 discipine values, (5)values social, (6) the value of cultural education, and (7) the value of hard work.